Long-term antiretroviral therapy mitigates mortality and morbidity independent of HIV tropism: 18 years follow-up in a women's cohort. (15th November 2022) - Weiser, Barbara; Shi, Binshan; Kemal, Kimdar; Burger, Harold; Minkoff, Howard; Shi, Qiuhu; Gao, Wei; Robison, Esther; Holman, Susan; Schroeder, Tamara; Gormley, Alissa; Anastos, Kathryn; et al.
Abstract : Objective: CXCR4 (X4)-tropic HIV-1 was found previously to herald CD4 + cell depletion and disease progression in individuals who were antiretroviral-naive or took combination antiretroviral therapy (cART) for less than 5 years. We updated this finding by investigating whether the deleterious effect of X4-tropic strains is mitigated by long-term cART. Design: We examined morbidity and mortality in relation to HIV-1 tropism and cART in 529 participants followed up to 18 years in the Women's Interagency HIV Study; 91% were women of color. Methods: Plasma-derived HIV-1 tropism was determined genotypically. Results: We categorized participants according to the number of visits reported on cART after initiation. Group 1: three or less visits, 74% of these participants reporting no cART; group 2: at least four visits and less than 70% of visits on cART; group 3: at least 70% of visits on cART. AIDS mortality rates for participants in each group with X4 virus compared with those with R5 virus exclusively were, respectively: 62 vs. 40% ( P  = 0.0088); 23% vs. 22% [nonsignificant (NS)]; 7% vs. 14% (NS). Kaplan–Meier curves showed accelerated progression to AIDS death or AIDS-defining illness in participants with three or less cART visits and X4 viruses ( P  = 0.0028) but no difference in progression rates stratified by tropism in other groups. Logistic regression found that HIV-1 suppression for at least 10 semiannual visits (≥5 years total) mitigated X4 tropism's deleterious effect on mortality, controlling for maximal viral load, and CD4 + nadir. Conclusion: Long-term cART markedly mitigated the deleterious effect of X4 viruses on AIDS morbidity and mortality. Mitigation was correlated with duration of viral suppression, supporting HIV-1 suppression as a crucial goal.